(untitled) (Journal of Nobel Medical College, 2017)
Background : Hepatorenal Syndrome (HRS) is a serious complication of liver cirrhosis with critically poor prognosis with treatment currently based on vasopressors. We aimed to study the safety and effects of Intravenous Noradrenaline in patients with Type 1 HRS and also to define factors predictive of a response. Materials and Methods: It was a prospective observational study conducted in a tertiary care hospital in Eastern Nepal enrolling patients withType 1 HRSfrom 2014 to 2015. All patients received Noradrenaline (0.5-3 mg/hr, intravenously) and albumin (1 g/kg followed by 20–40 g/day). Primary outcome was improvement of renal function. Results : 60 Type 1 HRS patients were enrolled in the study -37 males (61.7%) and 23 females (38.3%), mean age 58.18±9.33 years. The therapy was well tolerated as only 6.7% of patients withdrew treatment. Reversal of HRS was observed in 38 patients (63.3%) with the mean duration of 6.39±1.33 days. Of the baseline variables, higher urine output, higher mean arterial pressure and lower serum creatininewere predictive of response. Multivariate analysis showed Mean arterial pressure to be an independent variable of response (adjusted odds ratio 0.588, 95% CI- 0.393-0.880, P>0.05). Finally mean arterial pressure had a negative correlation with serum creatinine and a positive correlation with Urine output. Conclusion : Noradrenaline and albumin are safe and effective in improving renal function in patients with Type 1 HRS.There is a need for studies with larger sample size to correlate improvement in renal function with overall survival. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), page: 20-28